Studying the Interstellar Medium of H II/BCD Galaxies Using IFU Spectroscopy - Patricio Lagos; Polychronis Papaderos (Advances in Astronomy, 2013)
We review the results from our studies, and previous published work, on the spatially resolved physical properties of a sample of H ii/BCD galaxies, as obtained mainly from integral-field unit spectroscopy with Gemini/GMOS and VLT/VIMOS. We confirm that, within observational uncertainties, our sample galaxies show nearly spatially constant chemical abundances similar to other low-mass starburst galaxies. They also show He ii  λ4686 emission with the properties being suggestive of a mix of excitation sources and with Wolf-Rayet stars being excluded as the primary ones. Finally, in this contribution, we include a list of all H ii/BCD galaxies studied thus far with integral-field unit spectroscopy.